Configuring Citrix MetaFrame XP for Windows including future release 1 - Broomes, Chris. (Syngress Media, 2002)
Syngress's best-selling Citrix MetaFrame author to delivers world class support for this new product As the newest member of the Citrix MetaFrame product family, Citrix MetaFrame XP and recent add-on Feature Release 1 is making a slash in the IT community. Configuring Citrix MetaFrame XP for Windows offers system administrators and network engineers an in-depth look at configuring, optimizing, implementing and troubleshooting their Windows applications deployed using Citrix MetaFrame XP. Real-world examples and step-by-step exercises will help system administrators maxinise the capabilities of this revolutionary product from Citrix. The only book to-date to provide comprehensive coverage of the eagerly awaited Feature Release 1 add-on Citrix MetaFrame is a rapidly growing technology; as companies adopt thin-client technology, the number of Certified Citrix Administrators (CCAs) is set to skyrocket Unrivalled web based support at solutions@syngress.com.